The pepsins from human gastric mucosal extracts - Etherington, D. J. (1970)
1. The pepsins and pepsinogens of the gastric mucosal extracts of two normal subjects, of seven patients with gastric adenocarcinoma and of two patients with duodenal ulcer have been investigated by agar-gel electrophoresis and by ion-exchange chromatography. 2. Of the eight zones of proteolytic activity that have previously been reported in normal human gastric juice, seven can be detected in activated fundic mucosal extracts. Of these seven, four can be attributed to discrete pepsins, numbered 1, 3a, 3 and 5. 3. Zone 7 results from the activity of one or more enzymes that are alkali-stable and are best referred to as gastric proteinases rather than as pepsins. Zone 7 is much more evident in mucosal extracts than in gastric juice. 4. Zones 4 and 6 may result respectively from the activity of a pepsin–inhibitor complex and of an unactivated zymogen. 5. It was not possible, by the chromatographic methods employed, to separate satisfactorily the individual pepsins from activated extracts or their precursors from unactivated extracts, so that the ascribing of a pepsin to a specific zymogen must be considered tentative. Even so, pepsin 3 appears to arise from at least two major precursors, if not from three, whereas pepsins 1 and 5 each arise from a single major precursor. 6. Pyloric mucosal extracts contain principally zone 5 but also zones 6 and 7. These zones in general behave similarly to the corresponding zones of fundic extracts, but pyloric pepsin 5 migrates slightly faster on agar-gel electrophoresis than does fundic pepsin 5 and is a different enzyme. Zones 1 to 4 are absent.